2015
DOI: 10.5937/ekonomika1504089n
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to innovation in SMEs in the Republic of Serbia

Abstract: Часопис излази четири пута годишње ИЗДАВАЧ: Друштво економиста "Економика" Ниш СУИЗДАВАЧИ: Економски факултет у Приштини, Факултет за услужни бизнис-Сремска Каменица, Институт за економику пољопривреде-Београд, Факултет за пословне студије и право-Београд, Факултет за трговину и банкарство, Универзитет Алфа-Београд, Савез економиста Србије-Друштво економиста Ниш.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Studies have revealed that small and medium-sized enterprises (SMEs) have a lack of interest in practicing environmental and sustainability practices because of poor financial situations (Khattak 2020;Memon et al 2020). Moreover, it has also been scrutinized that a lack of financing hinders SMEs from investing in advanced technologies and innovative activities (Nikolić et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that small and medium-sized enterprises (SMEs) have a lack of interest in practicing environmental and sustainability practices because of poor financial situations (Khattak 2020;Memon et al 2020). Moreover, it has also been scrutinized that a lack of financing hinders SMEs from investing in advanced technologies and innovative activities (Nikolić et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SMEs can experience a wide-ranging set of difficulties during transition periods that negatively impact their business operations (Nikolić et al, 2015). In a study regarding the transition of the Serbian economy by Jovanović et al (2018) it was shown that policy makers should encourage and facilitate SMEs' effective responses to change; however, the article also emphasises that SMEs themselves must address the challenges via effective change management.…”
Section: Results and Discussion: Critical Change Factors For Smesmentioning
confidence: 99%
“…This type of innovation is occurring mostly in large companies that may have significant resources [13], but for small entrepreneurs it will be very difficult to reach these levels [14], while current conditions are preserved [15]. The aspects compiled in these results show great interest on the part of small entrepreneurs to innovate [16], the progress achieved confirms that innovation is a component that is being positioned in business management [17], however, tax and economic demands and access to sources of financing [18] may be factors that impact the process and delay it in comparison with the expected advances.…”
Section: Fig 4: Product Innovationmentioning
confidence: 85%